Welcome to the neighborhood: dismantling xenophobia while building community at the Lower East Side Tenement Museum - Whittenburg, Cari, author; Dickinson, Greg, advisor; Knobloch, Katherine, committee member; Aoki, Eric, committee member; Aronis, Carolin, committee member (Colorado State University. Libraries, 2025)
Few issues occupy U.S. political, social, and cultural discourse like immigration. Since the earliest days of the U.S. as a nation, immigration has been a subject of contention and an important point of public discussion. Popular rhetoric about immigration works to exacerbate xenophobia and present immigrants as the antithesis of American values. In this dissertation, I argue that the Tenement Museum works to dismantle xenophobia through a rhetoric of neighborliness. This neighborliness combines ideologies of mutual respect and social responsibility that in turn work to negotiate the tension of difference and create networks of support. As visitors move through the museum's guided tours, both in the recreated tenement homes and the neighborhood, and participate in the engagement practices, they are asked to become neighbors with the families represented and immigrants at large. This embodied neighborliness invites visitors to bring immigrants into their community and assume a level of responsibility for their wellbeing while simultaneously reaffirming heteronormative family structures as the framework of who is deserving of care.
Keywords: mixed methods; neighborliness; space and place; museum studies; immigration; public memory